2018
DOI: 10.1016/j.anbehav.2017.11.025
|View full text |Cite
|
Sign up to set email alerts
|

Field experiments with wild primates reveal no consistent dominance-based bias in social learning

Abstract: Directed social learning suggests that information flows through social groups in a nonrandom way, with individuals biased to obtain information from certain conspecifics. A bias to copy the behaviour of more dominant individuals has been demonstrated in captive chimpanzees, but has yet to be studied in any wild animal population. To test for this bias using a field experiment, one dominant and one low-ranking female in each of three groups of wild vervet monkeys was trained on alternative methods of opening a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 43 publications
3
19
0
Order By: Relevance
“…Our results offer strong evidence that new box opening techniques spread through social transmission in groups of wild vervet monkeys, consistent with previous findings using two-option designs 27,44 . We found that (i) observing one option increases the probability of learning it, (ii) individuals who learned one option are 31x are more likely to subsequently learn the other option, and (iii) females tended to socially learn twice as fast as males.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our results offer strong evidence that new box opening techniques spread through social transmission in groups of wild vervet monkeys, consistent with previous findings using two-option designs 27,44 . We found that (i) observing one option increases the probability of learning it, (ii) individuals who learned one option are 31x are more likely to subsequently learn the other option, and (iii) females tended to socially learn twice as fast as males.…”
Section: Discussionsupporting
confidence: 91%
“…The single performance bias towards higher rankers does not explain the overall bias from higher rankers to lower rankers because we found evidence of a social information use bias, with observations of higher-ranked individuals having a greater effect on the rate at which behavior is socially learned. This is in accordance with an earlier study 27 , in which it was found that the dominant models' demonstrations did not elicit more observations than the lowranking ones, but interestingly they reported high-ranking females showed a significant bias to copy the dominant female. In that study the authors used a two-option design and trained two models of differing ranks in each group: one was the highestranked female and the other one was a female of mid to low rank.…”
Section: Wild Vervet Monkeys Socially Learn a Novel Foraging Techniquesupporting
confidence: 93%
See 2 more Smart Citations
“…neuroscience (Woods et al 2011;Mendell et al 2014), social learning (Botting et al 2018) and sexual selection (Borgeaud et al 2015;Rodríguez et al 2015), and these studies require a clear understanding of genetic boundaries and connectivity between populations, using both neutral and adaptive markers. Vervet monkeys also often find their way to primate rehabilitation centres following human primate conflicts (Wimberger et al 2010) and re-introduction of these animals to suitable recipient populations without considering the provenance of the rehabilitated animals should be discouraged.…”
Section: Introductionmentioning
confidence: 99%